Perspectives in total hip arthroplasty advances in biomaterials and their tribological interactions - Affatato, Saverio (Woodhead Publishing series in biomaterials, 2014)
Total hip arthroplasty, the most commonly performed orthopaedic procedure, is used to replace or reconstruct the hip with an artificial joint. Perspectives in Total Hip Arthroplasty outlines developments in technologies and biomaterials used for this procedure, with a focus on the tribological interactions of the materials used. Part one outlines the history of total hip arthroplasty and goes on to explore advances in techniques and biomaterials. Part two focuses on the tribology of materials used to perform this procedure, providing an explanation of the impact of wear on th